Frequency of Pre-Analytical Errors and Its Causes in Glucose Specimen Collection: A Cross-Sectional Analysis in Bahawal Victoria Hospital, Pakistan - Hafiz, Hafiza Asma; Naseer, Muhammad Umair; Tanvir, Seemi; Kalhoro, Raima; Hafeez, Misbah; Zia, Memona (Pakistan journal of medicine and dentistry, 2025)
Background: The laboratory testing process comprises the pre-analytical, analytical, and post-analytical phases. The pre-analytical phase has the highest frequency of error among these three stages. The purpose of the study was to determine the prevalence of pre-analytical errors and the reasons behind them in the collection of glucose specimens. Methods: This descriptive cross-sectional study (039-DME-QAMC) was carried out on 225 samples collected at the Pathology Department of Bahawal Victoria Hospital in Bahawalpur between July and December of 2024.  The method of non-probability sequential sampling was applied. Samples from indoor departments, patients who did not give their informed consent, and any stored specimens were not included. All information on pre-analytical problems, including hemolyzed samples, quantity insufficient, improper centrifugation, delayed processing, and labeling errors, has been meticulously documented by the lead researcher in the proforma. During the data collection process, quality control procedures were in place to ensure accuracy and consistency.  SPSS Ver. 25 was used to enter and analyze all of the data. The data's normality was examined using the Shapiro-Wilk test. Results: In this study, frequency of preanalytical errors in glucose specimen collection process is 20% with delayed specimens (9.3%, n=21) is the most common, while other errors like inappropriate centrifugation (3.1%, n=7), hemolyzed samples (2.7%, n=6) and sample quantity insufficient (QNS) were 1.8% (n=4). Conclusion: This study highlighted the need for sodium fluoride tubes for the delayed processing specimens to prevent in vitro glycolysis, proper blood collection techniques, and timely specimen handling in proper ways to minimize errors.